Robust finite-time H∞ control of linear time-varying delay systems with bounded control via Riccati equations - Piyapong Niamsup (2018)
© 2017 Institute of Automation, Chinese Academy of Sciences and Springer-Verlag Berlin Heidelberg In this paper, we will present new results on robust finite-time H ∞ control for linear time-varying systems with both time-varying delay and bounded control. Delay-dependent sufficient conditions for robust finite-time stabilization and H ∞ control are first established to guarantee finite-time stability of the closed-loop system via solving Riccati differential equations. Applications to finite-time H ∞ control to a class of linear autonomous time-delay systems with bounded control are also discussed in this paper. Numerical examples are given to illustrate the effectiveness of the proposed method.